The Hydrothermal Synthesis of Quantum and Carbon Dots - Hertsig, Karlijn (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2026)
In the context of the global energy transition, this thesis explores the hydrothermal synthesis of energy materials, specifically quantum dots and carbon dots, emphasising sustainable green chemistry approaches, as introduced in Chapter 1. Chapter 2 details the hydrothermal synthesis of cadmium sulfide quantum dots (CdS QDs) using water as a solvent and reduced reaction temperatures. After systematic investigation of reactants, pH, molar ratio, and reaction time, excellent control over the optical properties and size of CdS QDs was achieved. Simplifying the reaction system to a cadmium source and a bifunctional ligand resulted in a 36% reduction in material input (in moles). Chapters 3 and 4 address the synthesis of carbon dots (CDs) from seaweed and its derivatives as a sustainable alternative to metal-based quantum dots. Chapter 3 investigated the hydrothermal synthesis of blue emissive CDs from seaweed at 160 °C/4 h, identifying challenges in purification and stability due to aggregation and side product formation. Consequently, Chapter 4 focused on optimising hydrothermal reaction parameters for six seaweed precursors using the Response Surface Method (RSM). This optimisation identified optimal reaction temperatures ranging from 180 °C to 210 °C and reaction times from 4 to 6 h. These optimised conditions significantly enhanced quantum yields (QYs) and photoluminescence compared to the standard conditions of 160 °C/4 h, with notable improvements observed for kelp and Irish moss when processed at 210 °C/4 h, with 139 and 114% respectively. Overall, this work demonstrates the successful application of green chemistry principles, utilising water as a solvent, reducing reaction temperatures, and leveraging renewable biomass for the sustainable production of quantum and carbon dots. Using reaction optimisation method RSM for carbon dots synthesis is proposed to overcome isolation challenges and facilitate post-synthesis processing. This approach contributes to the development of eco-friendly nanomaterials crucial for advancements in renewable energy technologies.
APPROVED
Keywords: Hydothermal; Quantum Dots; Carbon Dots; Green Chemistry